The role of the principle in the legal order in Indonesia - Muhammad Hasan; Nida Kristinawati; Heru Kuswanto (Faculty of Law, Merdeka University Surabaya, Indonesia, 2020)
In the formation of regulations in Indonesia, it cannot be separated from the name of the principle of law because it includes the fundamental in forming a regulation so that it does not conflict with existing regulations, or with terms that are in the law, namely truth coherence. The principle of law is an important element of a rule of law, it can even be said to be the 'heart' of the rule of law. The principle of law will remain and will give birth to further regulations. Ultimately, the principle of law has a dual function, namely as the foundation of a positive legal system and as a critical test stone to the prevailing positive legal system. How does the binding force of the validity of the legal principle and what if there is the principle of law that is contrary to the principle of law. The research method used in this study is normative juridical, with two approaches namely; statute approach and conceptual approach, as for the formulation of the problem in this research is what should be done if the principle is contrary to the principle? The results of this study are that even though the principle contradicts the principle, the solution is to use the principle as a basis in a regulation that is made and see also the conflicting rules for what are the contradictions.